Investigation of antimicrobial effect of crude extract and three sub-fractions of Platychaete aucheri (Boiss.) Boiss against five standard microbial strains and clinical Escherichia coli isolates - Tina Zabihi- Nik; Mojdeh Hakemi-Vala; Fatemeh Baghery Bejestany (Islamic Azad University, Shahrekord Branch, 2017)
Background & Aim: Platychaete aucheri (Boiss.) Boissis one of the Persian endemic plants and it belongs to Asteraceae family. The present study was aimed to evaluate the antimicrobial activity of crude methanolic extract and three sub-fractions of the flowering aerial parts of Platychaete aucheri against some gram-positive and gram-negative standard bacteria, Candida albicans and clinical Escherichia coli isolated from urinary tract infections (UTIs) and burn wounds. Experimental: Total methanolic extract of P.aucheri was prepared by maceration method.Further chloroform, petroleum ether and aqueous fractions were obtained by using liquid-liquid extraction method. Antimicrobial effect examined by well diffusion and broth microdilution method based on the CLSI protocol. The standard tested microbial strains included Escherichia coli PTCC 1399, Pseudomonas aeruginosa PTCC 1430, Staphylococcus aureus PTCC1431, Bacillus cereus PTCC 1247 and Candida albicans PTCC 5027. Also, extract and fractions were tested against Escherichia coli isolates from urine samples and burn wounds of patients from Imam Khomeini and Shahid Motahari Hospitals of Tehran (Iran) during 2013 and 2014 respectively. Results: Total extract and fractions had ability to prevent microbial growth. Total methanolic extract, chloroform and petroleum ether fractions demonstrated moderate antimicrobial activity against standard P.aeruginosa and E.coli with MIC values in the range of 35-42 mg/ml. MIC values against clinical isolates of E.coli were in the range of 60-72 mg/ml. The aqueous fraction showed lower antimicrobial activity in comparison to total extract and other fractions against standard and clinical isolates. Results confirmed that petroleum ether and chloroform fractions had relatively more anti bacterial activity than total methanolic extract and aqueous fraction. Recommended applications/industries: Based on the non toxicity results in future studies, this plant can be used as a natural antibacterial source for therapeutic products to help UTIs and wounds treatment.